Impact Promotion on Awareness Product and Organizational Performance : Case Study of the Mineral Water Industry - Zuniarti, Ida; Rusiyati, Sri; Karlina, Eulin; Rukiastiandari, Sinta; Ariawan, Joko; Zahra, Zahra (Dinasti Publisher, 2024)
Research This aim For investigate impact promotion on awareness product , goal organization , determination price products , and revenue sales in the mineral water industry on Lombok Island , with focus on PT. Narmada Drinking Water . Study use method survey with data collection via questionnaire to 121 respondents who were staff company . Research result show that promotion own significant relationship _ with all variables studied . _ First , promotion impact positive on awareness product , where changes by 1% in activity promotion can cause change of 52.7% in awareness product . This shows the importance of promotional strategies in introduce product to market and create awareness more products _ high among _ consumer . Second , promotion also has an impact significant for the purpose organization , with change by 1% in promotion can cause change of 89.6% in achievement objective organization . This confirms that promotion is tool important in reach objective organization in a way whole . Third , results study indicated that promotion influence determination price product or brand company . Companies need consider promotional strategies they in connection with price product For reach optimal and maximizing balance mark brand they . Lastly , promotion own impact positive on income sale company , which confirms that the promotional strategy is effective can help increase performance sale . Study This give outlook important about role promotion in reach various objective business . The implications is that company need designing and implementing appropriate promotional strategies _ For reach objective they . along with market and technological developments , companies must Keep going reviewing and updating promotional strategies them to stay relevant and effective in reach objective business that has set .